Intermittent preventive treatment of malaria in pregnancy: a new delivery system and its effect on maternal health and pregnancy outcomes in Uganda - A K Mbonye; I C Bygbjerg; P Magnussen (The World Health Organization, 2008)
OBJECTIVE: To assess whether traditional birth attendants, drug-shop vendors, community reproductive-health workers, or adolescent peer mobilizers could administer intermittent preventive treatment (IPTp) for malaria with sulfadoxine-pyrimethamine to pregnant women. METHODS: A non-randomized community trial was implemented in 21 community clusters (intervention) and four clusters where health units provided routine IPTp (control). The primary outcome measures were access and adherence to IPTp, number of malaria episodes, prevalence of anaemia, and birth weight. Numbers of live births, abortions, still births, and maternal and child deaths were secondary endpoints. FINDINGS: 1404 (67.5%) of 2081 with the new delivery system received two doses of sulfadoxine-pyrimethamine versus 281 (39.9%) of 704 with health units (P < 0.0001). The prevalence of malaria episodes decreased from 906 (49.5%) of 1830 to 160 (17.6%) of 909 (P < 0.001) with the new delivery system and from 161 (39.1%) of 412 to 13 (13.1%) of 99 (P < 0.001) with health units. Anaemia was significantly less prevalent in both arms. There was a lower proportion of low birth weight 6.0% with the new delivery system versus 8.3% with health units (P < 0.03). Few abortions and stillbirths were recorded in either arm. Fewer children and women who accessed IPTp with health units died than in the intervention group. CONCLUSION: The new approaches were associated with early access and increased adherence to IPTp. Health units were, however, more effective in reducing parasitaemia and malaria episodes. We recommend further studies to assess programming modalities linking the new approaches and health units.